PERENCANAAN PENGEMBANGAN PARIWISATA PANTAI LON MALANG KABUPATEN SAMPANG - Rina Nur Azizah; Nurhaliza Fardayanti (Faculty of Social and Political Science, 2021)
Lon Malang beach tourism has several problems in the tourism development process, including inadequate facilities and infrastructure. Tourism planning is the process of making plan, strategy, recreational purpose development, and the study of tourism uniqueness visited in a temporary period. According to Paturusi (2008:27), tourism planning is a decision-making process related to the future of tourism destination. This is a dynamic process of goal setting, which systematically considers and evaluates selected alternatives. According to Oka A. Yoeti (1997:1), there are five indicators of tourism planning aspects, namely: tourists, transportation, tourism attraction, marketing, and human resources. This research uses descriptive qualitative with data analysis technique model from Creswell (2014) which consists of six steps of data analysis: First, processing and preparing data for analysis. Second, reading the entire data. Third, coding the data. Fourth, applying the coding process to describe the settings (domain), people (participants), category, and the theme being analyzed. Fifth, Indicating how the description and theme will be restated in the narrative/report. Finally, interpreting the data analysis. The results shows that five indicators are included, such as tourists, transportation, attractiveness, marketing and human resources. They are still inadequate in planning the tourism development of Lon Beach Malang in Sampang. The conclusion from the planning of tourism development is applied well because there are several factors that can hinder the planning of future tourism development.